The PrP genotype of sheep of the improved Valachian breed - Tkáciková, L; Hanusovská, E; Novák, M; Arvayová, M; Mikula, I (Folia microbiologica, 2003)
In a worldwide majority of sheep breeds an excessive susceptibility to scrapie associated with the PrP gene alleles coding for valine (V; at the 136 codon) and glutamine (Q; at the 171 codon) (e.g., VRQ/VRQ, VRQ/ARQ, or ARQ/ARQ) was demonstrated. Particularly the PrPVRQ allele is closely associated with the high-risk development of the disease; the PrPARQ allele can also fulfill this function but under certain limited conditions. Polymorphism in the PrP gene sequences (conclusively related to the increased susceptibility of sheep to scrapie) of improved Valachian sheep from two Slovak regions, Orava and Spis, was determined. Examination of 735 sheep showed that ARR/ARQ was the most frequent genotype (45.2%). High-risk genotypes were determined in 32.4% of sheep (ARQ/ARQ 19.3, ARR/VRQ 9.0, ARR/VRQ 3.5, VRQ/VRQ 0.3, ARR/VRR 0.3). Low-risk genotypes were found in 67.7% of sheep (ARR/ARQ 45.2, ARR/ARR 10.9, ARR/AHQ 5.7, ARQ/ARQ 4.9, AHQ/AHQ 0.7, ARR/AHR 0.3). Despite the geographically distant flocks of improved Valachian sheep investigated no difference in the occurrence of individual PrP genotypes was observed.
Keywords: sekvence nukleotidů; polymerázová řetězová reakce; Male; Breeding; Genetic Predisposition to Disease; Slovakia; Scrapie; Slovenská republika; Genotype; polymorfismus genetický; Prions; Sequence Analysis, DNA; sekvenční analýza DNA; priony; mužské pohlaví; ovce; nemoci ovcí; Sheep; chov; Polymorphism, Genetic; Animals; scrapie; ženské pohlaví; Sheep Diseases; zvířata; polymorfismus délky restrikčních fragmentů; genotyp; Polymerase Chain Reaction; Base Sequence; Alleles; Female; alely; genetická predispozice k nemoci; Polymorphism, Restriction Fragment Length